AB0167 SINGLE CELL RNA EXPRESSION IN LUPUS NEPHRITIS COMPARING AFRICAN-AMERICAN AND CAUCASIAN PATIENTS IDENTIFIES DIFFERENTIAL EXPRESSION OF TYPE I INTERFERON PATHWAY. (June 2019) - Fava, Andrea; Zhang, Yuji; Hacohen, Nir; Arazi, Arnon; Berthier, Celine; Rao, Deepak; Brenner, Michael; Wofsy, David; Davidson, Anne; Kretzler, Matthias; Hildeman, David; Steve Woodle, E.; et al.
Abstract : Background: African-American ethnicity is associated with a 3-fold higher risk of developing systemic lupus erythematosus (SLE). In addition, there is an increased risk of lupus nephritis (2-fold), high-risk histological features, and resistance to treatment. This may account for the increased mortality rate compared to Caucasian patients, especially in women. Objectives: In Phase One of the Accelerating Medicines Partnership (AMP) study, we used single-cell RNA sequencing on kidney biopsies from patients with active lupus nephritis to identify pathways that were differentially expressed in African-American patients. Methods: Single cell RNA sequencing was performed on renal biopsies obtained for clinical purpose for active nephritis using CEL-Seq2. Cell clusters with similar expression profile were identified using t-distributed stochastic neighbor embedding (t-SNE). First, the relative abundance of a cluster in AAs compared to Caucasian was determined using a logistic mixed model. Second, the differential expression profile was determined for each cell cluster and we applied Ingenuity Pathway Analysis (IPA) (QIAGEN Bioinformatics) to identify pathways of interest. Results: Samples from 13 AA and 7 Caucasian patients were obtained. Of the 3097 sequenced cell libraries, we used 2354 which passed our quality filter for a total of 30155 unique molecular identifiers. We identified 16 cell clusters including CD4, CD8, B and plasma cells, NK, myeloid cells, and tubular cells. We identified 2 cell clusters unique to African-American patients, a T and a B cell population with high expression of interferon inducible genes. We also identified that same cell populations may have differential gene expression profiles across ethnicity. For example, CD4 T cells in African-Americans have a higher expression of type 1 and type 2 interferon pathways. In contrast, myeloid cells have several upregulated pathways in Caucasians, including ERK/MAPK signaling. Conclusion: African-American lupus nephritis patients may have a stronger interferon pathway activation in infiltrating immune cells. Several other pathways, including ERK/MAPK, are differentially expressed in infiltrating cells based on ethnicity. These results suggest that ethnicity might predict a response to both current and upcoming treatments, paving the way for a more personalized approach to treatment in lupus nephritis. Further work in Phase 2 of AMP will confirm and extend these findings. Disclosure of Interests: Andrea Fava: None declared, Yuji Zhang: None declared, Nir Hacohen: None declared, Arnon Arazi: None declared, Celine Berthier: None declared, Deepak Rao: None declared, Michael Brenner Grant/research support from: Roche: sponsored research agreement on stromal cells (but has nothing to do with checkpoint related disease), Consultant for: GSK: consultant. (I am part of their immunology network, a group of about 8 immunologists who advise them regularly and broadly in the areas of inflammation and infection)., David Wofsy Consultant for: GlaxoSmithKline – Member, data safety monitoring board Novartis – Member, data safety monitoring board Celgene – member, scientific advisory board, Anne Davidson: None declared, Matthias Kretzler: None declared, David Hildeman: None declared, E. Steve Woodle: None declared, Betty Diamond: None declared, Michelle A Petri Shareholder of: Pfizer, Merck, Grant/research support from: AstraZeneca, Exagen, Consultant for: Eli Lilly, GSK, Merck EMD Serono, Janssen, Amgen, Novartis, Quintiles, Exagen, Inova Diagnostics, AstraZeneca, Blackrock, Glenmark, UCB, and the Annenberg Center for Health Sciences